Plastificación interna con bio-aceites epoxidados de ácido poliláctico (PLA) para productos básicos procesados por inyección o extrusión (2013)
The planet's environment is currently experiencing drastic changes in its composition, mainly due to the way of life of man. While it is true there is uncertainty about the causes of some changes, it is certain that the man is directly connected with several of them; the three most important being the increase in the concentration of carbon dioxide in the atmosphere, alterations in the biogeochemistry of the nitrogen cycle globally and the mineral structure of the earth. (Voustek, 1994). The effects of global warming that translate these changes have been shown more strongly in recent times. The above, added to the uncertainty about the remaining fossil fuels on Earth (non-renewable resource), have motivated a series of evolutions in technological development that seek to replace these fuels or make their consumption more efficient (better designed machines, modified biodiesel case fuels for example). This is where biopolymers appear within a set of new solutions. Nature produces about 170,000 million tons per year of renewable carbon in the form of 'biomass', currently only about 3% of it is used in the food sector and other applications, but with this resource a large percentage of the demand for petroleum derivatives. The challenge is to convert the complex chemical structures into structures that are useful for the different purposes of man. (Pilla S., 2011). One of the great products of nature in this sense is starch (found in the form of corn, potatoes, rice and wheat among many other products), rich in carbon. The use of this compound has the disadvantage that carbon is trapped within the macromolecular networks that compose it, there industrial chemistry requires processes that simplify such networks to produce ethanol (with great potential as a biofuel). and lactic acid (an important element of this research). (Pilla S., 2011). Precisely, the object of study of this research is a derivative of this last product: polylactic acid (PLA), which in principle is obtained by the synthesis of lactic acid that comes worldwide between 70% and 90% of fermentation of products such as starch and sugar mainly (Siebert-Raths & Enders, 2011) with a process like the one shown in Figure 1. One of the drawbacks of the use of PLA is its high modulus of elasticity and its low deformation in the fracture, so researchers have proposed different ways to combine it with various types of materials, to ensure that the polymer can meet applications that currently make products made with LDPE, HDPE, PET, PS among others.